Analysis of Islamic Processing Messages in the Film of Nyai Ahmad Dahlan by Dyah Kalsitorini (Charles Sanders Peirce’s Semiotic Model) - Trimurti, Asih Ananda; Irfanudin, Fahmi (Journal of Islamic Communication and Counseling, 2023)
The film is a medium of communication as well as an effective medium of da’wah and can be well received by all levels of society, especially Muslims. Nyai Ahmad Dahlan film is a biopic film that tells the story of the life journey of Siti Walidah, who is often known as Nyai Ahmad Dahlan. This research aims to find out what da’wah messages are in the Nyai Ahmad Dahlan film. The researcher uses the semiotic analysis of Charles Sanders Peirce, using three stages: the sign, the use of the sign (interpretant), and the reference sign (object). This study uses a descriptive qualitative method using a data analysis approach to answer the problems formulated. The data is obtained from several scenes that refer to the message of da’wah and similar previous studies. From the research that has been conducted, it is concluded that the Nyai Ahmad Dahlan film contains several messages of Islamic da’wah, including messages of aqidah (belief), moral messages, and sharia messages in the form of muamalah (relations between humans).